Quality and performance of Papanicolaou test using the clinical and laboratory standards institute (CLSI) EP12-A2 guidelines: A single-center study in Peru - Moya-Salazar, J (2023)
Context: Quality assurance in cervical cytology is based on the cyto-histological correlation that is performed in several countries even without standardized protocols. Aims: To evaluate the quality of the Pap smear with the Clinical and Laboratory Standards Institute (CLSI) EP12-A2 guideline in a Peruvian hospital. Settings and Design: This prospective study was carried out at tertiary care national hospital. Methods and Material: The 156 cyto-histological results were collected and coded according to the Bethesda 2014 and FIGO system. The evaluation with the CLSI EP12-A2 guide allowed estimating the performance and quality of the test. Statistical Analysis Used: We performed a descriptive analysis of the cytological and histological data and correlation with the weight Kappa test. From the calculation of the likelihood ratios, the post-test probability was estimated using Bayes' theorem. Results: In cytology, 57 (36.5%) were undetermined abnormalities, 34 (21.8%) low-grade squamous intraepithelial lesion (SIL), and 42 (26.9%) high-grade SIL. Of the total biopsies, 56 (36.9%) were cervical intraepithelial neoplasia (CIN) grade 1, 23 (14.7%) were both CIN grade 2 and 3. We determined sensitivity, specificity, a positive and negative predictive value of 94%, 74.6%, 58%, and 97.1%, respectively. We determined a moderate cyto-histological agreement (κ = 0.57). Atypical squamous cells of undetermined significance (40%), and cannot exclude high-grade squamous intraepithelial lesions (42.1%) that showed higher overdiagnosis results. Conclusions: The quality and performance of the Papanicolaou test show high sensitivity and moderate specificity. The concordance found was moderate and the proportion of underdiagnosis was higher in abnormalities of undetermined significance.